Supraglottic airway devices variably develop negative intrathoracic pressures: A prospective cross-over study of cardiopulmonary resuscitation in human cadavers. (1st March 2020) - Holley, Joe; Moore, Johanna C.; Jacobs, Michael; Rojas-Salvador, Carolina; Lick, Charles; Salverda, Bayert J.; Lick, Michael C.; Frascone, Ralph J.; Youngquist, Scott T.; Lurie, Keith G.
Abstract: Aim of the study: Negative intrathoracic pressure (ITP) during the decompression phase of cardiopulmonary resuscitation (CPR) is essential to refill the heart, increase cardiac output, maintain cerebral and coronary perfusion pressures, and improve survival. In order to generate negative ITP, an airway seal is necessary. We tested the hypothesis that some supraglottic airway (SGA) devices do not seal the airway as well the standard endotracheal tube (ETT). Methods: Airway pressures (AP) were measured as a surrogate for ITP in seven recently deceased human cadavers of varying body habitus. Conventional manual, automated, and active compression-decompression CPR were performed with and without an impedance threshold device (ITD) in supine and Head Up positions. Positive pressure ventilation was delivered by an ETT and 5 SGA devices tested in a randomized order in this prospective cross-over designed study. The primary outcome was comparisons of decompression AP between all groups. Results: An ITD was required to generate significantly lower negative ITP during the decompression phase of all methods of CPR. SGAs varied in their ability to support negative ITP. Conclusion: In a human cadaver model, the ability to generate negative intrathoracic pressures varied with different SGAs and an ITD regardless of the body position or CPR method. Differences in SGAs devices should be strongly considered when trying to optimize cardiac arrest outcomes, as some SGAs do not consistently develop a seal or negative intrathoracic pressure with multiple different CPR methods and devices.